UKRAINIAN NATION ON THE PAGES OF UKRAINIAN DIASPORA’S FICTION OF THE 20-50S OF THE XXth CENTURY - Слоньовська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the mythological notion of mythema, mythologema, frame, pattern, concept, archetype. Image of nation-virgo. Colonized nation as harlot and slave in Yevhen Malaniuk’s prose. Nation as a colonizer and a colonized nation in the novel «Defeat» by Ivan Bahrianyi. Political nation as the final phase of the mature and self-sufficient nation. National idea in the structure of the vitalistic national myth.